The effectiveness of religious character building for Karangdukuh Elementary School students by making them habit of reading Asmaul Husna - Putri, Dhian Riskiana; Muslichah, Anniez Rachmawati; Arianti, Endah Fajri; Salsabila, Azzahra Anggun (Privietlab, 2026)
This study aims to determine the effect of developing the religious character of students at Karangdukuh Elementary School through the habitual recitation of the Asmaul Husna (The Beautiful Names of Allah). Asmaul Husna is a phrase containing good and noble qualities. The recitation of Asmaul Husna is performed every morning before the start of teaching and learning activities in the school. This activity aims to instill the good qualities of Asmaul Husna in students' personalities. This program of habitual daily recitation of Asmaul Husna is expected to foster good qualities in students, as embodied in the content of the Asmaul Husna. This study used a qualitative approach and ethnographic methods. There were three respondents in this study. Data collection was conducted through observation and interviews. This study shows that the habitual recitation of Asmaul Husna before teaching and learning activities can improve students' religious character. This improvement in religious character is evident in students' habits of being more polite, respectful of teachers, diligent in prayer, loving, and maintaining cleanliness.